The application of a scale for sports cohesion on the players of the first class football clubs in Najaf Governorate - Shaheed Radhi, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The current research included the great position of sports cohesion, problem, goals, assignments and areas of research. The research community was identified with players from first-class clubs in the province of Najaf for the sports season (2019/2020) for a sample of (140) players. On the contributions, which included similar studies, then the method and tools that dealt with the method and procedures of field research, and through the existence of an unregulated local scale, the researcher decided to legalize and apply the scale (sports cohesion) to first -class club players, and then to identify the preference for sports cohesion between teams and for the benefit of any of the included teams Search. As for the results, the results were presented and discussed, and the researcher concluded that sports cohesion is relatively high for first-class football club players, with the possibility of setting special standards and determining standard levels of (sports cohesion) for players of first -class football clubs.